Rating of overall childbirth experience: A qualitative study of a quantitative measurement - Frida Viirman; Reidun Jidrot; Linn Lundström; Lisa Ljungman (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Overall childbirth experience scores are used both in research and in clinical settings. Since it is still not fully understood what assessment of childbirth experience on a single‐item numeric rating scale or visual analog scale represents, the aim of this study was to explore women's reasoning and thoughts when rating overall childbirth experience numerically. Material and Methods A qualitative interview study of 26 women was conducted using a think‐aloud technique at a university referral hospital in Sweden. A manifest qualitative content analysis was performed to generate categories and sub‐categories representing how women decided which single value should represent their experience of giving birth. Results Two main categories emerged from the analysis. The first, Strategies for choosing a number, reflects variations in how the women approached the rating scale itself and includes five sub‐categories, each relating to a different strategy: (1) Comparison, (2) Start from the maximum value, (3) Start from the middle, (4) Weigh certain experiences more heavily, and (5) A means to an end. The second category, Specific factors considered in the rating, includes four sub‐categories, representing groups of factors contributing to the final childbirth experience score: (1) The time period, (2) Events linked to strong emotions, (3) Perceived support, and (4) Previous expectations. What the women included in their overall childbirth experience was hence translated into a number, using strategies from the first category and factors from the second category. Conclusions The considerable variations in how women approach the rating scale, and what they include in the assessment of overall childbirth experience, suggest that not only the childbirth experience itself but also the reasoning when evaluating it, is multifaceted. A standardized phrasing of the question and a clear purpose for the evaluation is warranted to strengthen the validity of the measurement. When used clinically for identifying women in need of support after childbirth, the rating should be followed by a conversation about the experience of giving birth, independent of the value chosen.